2020
DOI: 10.1186/s12933-020-01023-6
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between carotid disease and retinopathy in diabetes: a systematic review

Abstract: Background: Since studies of the relationship between carotid disease and diabetic retinopathy (DR) have shown apparent inconsistencies, the aim of this study was to conduct a systematic review of available published data. Methods: Electronic databases were searched independently by two reviewers, according to an iterative protocol, for relevant articles. The search term used was "diabetes AND (carotid disease OR intima-media OR carotid plaque OR carotid stenosis OR carotid arterial disease OR carotid artery d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…In human, CCAO or CCAS is a devastating cause of ocular ischemic syndrome ( Faries et al, 2006 ). Ocular ischemia resulting from CCAO or CCAS has gradually received attention in that several ocular disorders, such as ischemic optic neuropathy, diabetic retinopathy and glaucoma, are suggested to be involved with cardiovascular diseases-associated retinal ischemic states ( Chou et al, 2018 ; Drinkwater, Davis & Davis, 2020 ; Harris et al, 1999 ; Osborne et al, 2004 ). Therefore, CCAO or CCAS has been attempted to develop animal models for such retinal ischemic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In human, CCAO or CCAS is a devastating cause of ocular ischemic syndrome ( Faries et al, 2006 ). Ocular ischemia resulting from CCAO or CCAS has gradually received attention in that several ocular disorders, such as ischemic optic neuropathy, diabetic retinopathy and glaucoma, are suggested to be involved with cardiovascular diseases-associated retinal ischemic states ( Chou et al, 2018 ; Drinkwater, Davis & Davis, 2020 ; Harris et al, 1999 ; Osborne et al, 2004 ). Therefore, CCAO or CCAS has been attempted to develop animal models for such retinal ischemic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…A community‐based study which excluded people with prior cardiovascular disease showed that any diabetic retinopathy was associated with CCA IMT >1 mm (OR 1.84) and the presence of carotid plaque 19 . Other clinic‐ and hospital‐based studies have found a similar positive association with IMT, 10,13 no association with IMT but positive associations with other measures of carotid disease, 20–22 and no association with any measure of carotid disease 5,23 …”
Section: Discussionmentioning
confidence: 94%
“…The results of studies assessing the association between diabetic retinopathy and carotid disease have been inconsistent 5 . This could reflect differences in participant sources, selection criteria, techniques of vascular assessment, and/or the availability of explanatory and confounding variables.…”
Section: Introductionmentioning
confidence: 99%
“…[ 22 ] However, the literature is equivocal about the exact nature of carotid vascular parameters associated with the presence or severity of DR as most of the studies have been cross-sectional. [ 23 ] We performed Doppler imaging of the internal carotid artery only in the cases with angiographic features of ocular ischemic syndrome, which was an exclusion criterion ( supra vide ), and therefore could not correlate this parameter with asymmetric DR in this series. These shortcomings need to be addressed by a larger, longitudinal study of FLR with noninvasive wide-angle diagnostic imaging and a more detailed systemic assessment to assess its natural course and long-term prognosis.…”
Section: Discussionmentioning
confidence: 99%